The Force Requirements for Tooth Movement Part II: Uprighting and Root Torque - Lee Brian W. (Australasian Orthodontic Journal, 1995)
In orthodontic treatment tooth root movement is essential, not only to ohtain mesio-distal paralleling of individual tooth roots, but also to achieve correct axial inclinations in relation to hasal bones and inter-incisal angles in the anterior segments. This article describes a pilot study in which paired teeth on opposite sides of the mouth and which required root paralleling as a part of orthodontic treatment, were subjected to known, moments of force. The forces were exerted using helical torsion springs of predetermined load-deflection characteristics. Average weekly moments of force were related to the weekly rates of angular movement of eight teeth in a group of four patients. The experiments lasted for up to seven weeks and were designed so that the movement of the paired teeth in each patient were concurrent.